Pemanfaatan Teknologi Telemetry Untuk Pengawasan dan Pengendalian Pencemaran Air Sungai - Djohar Samsi (Pusat Penelitian Informatika - LIPI, 2012)
A model of river water quality monitoring devices in accordance with the conditions of rivers in Indonesia is presented. The monitoring devices are easy to operate and maintain. Moreover, the monitoring devices are in accordance with the conditions of watershed in Indonesia, and support management functions of water resources. The methodology used is a field study in Citarum River, model development for water quality monitoring system using multiple sensors, data logger and data communications between module and flow cell development. Experiment result shows that a monitoring of the water river can be done remotely (from a distance) by telemetry technology.